Intermediation in Foreign Trade: When do Exporters Rely on Intermediaries? - Philipp J. H. Schröder; Harald Trabold; Parvati Trübswetter (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
The paper explores theoretically and empirically why trade intermediaries (TIs) are frequently used as agents for exports to some countries but not to others. We adapt a standard intra-industry trade model with variable export costs (e.g. transport) and fixed export costs (e.g. market access) to include a TI that is able to pool market access cost. From this framework explanatory factors for the TI share in a country?s exports are derived and subsequently tested with a new data set based on French customs information. The paper finds that: (i) higher market access costs increase the TI share, (ii) smaller export markets feature a larger TI share, (iii) the TI share is independent from variable (distance-dependent) export costs.
Keywords: F15; F12; F23; F10; D23; 330; trade intermediation; indirect exports; transaction costs; monopolistic competition; Exporthandel; Intraindustrieller Handel; Monopolistischer Wettbewerb; Internationale Markteintrittsstrategie; Transaktionskosten; Schätzung; Theorie; Frankreich